Insulin post-transcriptionally modulates Bmal1 protein to affect the hepatic circadian clock - Fabin Dang (Nature Portfolio, 2016)
The effect of the liver clock is modified by food entrainment via Bmal1/Clock core machinery. Here the authors show that insulin promotes postprandial Akt-dependent phosphorylation of Bmal1, resulting in association with 14-3-3 and Bmal1 shuttling out of the nucleus, thereby disrupting Bmal1 transcriptional effects on the clock.